(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The mulberry silkworm, or Bombyx mori L., is exceedingly delicate, extremely sensitive to changes in its surroundings, and incapable of surviving in harsh environments. The silkworm’s morphological and biochemical characteristics, including the diameter and weight of the cocoon, the length and weight of the larvae, and the protein content of the silk gland and cocoon, are impacted by seasonal variations.